Optical switching and nanothermochromic studies of VO₂(M) nanoparticles prepared by mild thermolysis method - Xu, Chang (2022)
Vanadium dioxide (VO2) has been widely studied due to its promising thermochromic property. VO2 nanoparticles film exhibits a unique nanothermochromic advantage with higher light transmittance (Tlum) and larger solar light transmittance modulation (∆Tsol) than continuous film. In this paper, a mild thermolysis method was developed to prepare VO2 nanoparticles with controlled size and morphology, which was then used to build the nanothermochromic films. By using vanadyl ethylene glycol (VEG) nanorods as a precursor, VO2 nanoparticles can be obtained at a thermolysis temperature as low as 250 °C within 5 min under static argon atmosphere. The VEG nanorods with uniform size and excellent dispersity were prepared from amorphous vanadium oxide nanopowders synthesized by electrochemical anodic-oxidation of vanadium target. The influence of the thermolysis conditions on the microstructure, phase transition and thermochromic properties of VO2 nanoparticles were investigated and discussed. By combining with transparent conductive substrate ITO, the VO2 nanoparticles films demonstrate an active optical switching performance, and the optimal thermochromic properties with Tlum of 48% and ∆Tsol of 11% can be achieved.